An approach for studies of mediator-induced leukocyte rolling in the undisturbed microcirculation of the rat mesentery - Yamaki, Kohji (1998)
1. Although intravital microscopy is the method of choice for observation of inflammatory leukocyte rolling and adhesion in small venules in vivo, a problem with this technique is that surgical exposure of suitable tissues per se triggers the rolling mechanism. In this study, we describe an approach to investigate induction of rolling in undisturbed microvessels. For this purpose, intravital microscopic observation of leukocyte rolling and adhesion in the rat mesentery was combined with histological determination of the intravascular concentrations of polymorphonuclear and mononuclear leukocytes (PMNL and MNL). 2. By relating the histologically determined number of intravascular leukocytes to either microvessel volume or to the erythrocyte concentration, the baseline MNL and PMNL content was found to be 3–6 fold higher in venules than in systemic blood. This increase in microvessel leukocyte concentration did not seem to be related to leukocyte-endothelium interactions, because the leukocyte concentration was similarly elevated in arterioles where rolling and adhesion did not take place. 3. Preparation of the rat mesentery for intravital microscopy time-dependently increased the venular PMNL concentration to over 100 fold the systemic PMNL concentration 45 min after exteriorization of the small intestine. The MNLs were much less responsive to the preparative manipulation. By treatment with the polysaccharide fucoidin (inhibits rolling but not firm adhesion per se), or by use of intravital microscopy immediately before tissue fixation, approximately 90% of the accumulated venular PMNLs were found to represent rolling cells. 4. Intraperitoneal injection of 10(−3)M histamine increased the venular PMNL (but not the MNL) concentration to almost 50 fold the systemic PMNL value. The histamine response did not vary with venular diameter, and the relative contribution of rolling vs firmly adherent cells to the PMNL, accumulation was again ≈amp;90%. Intraperitoneal injection of leukotriene C(4), but not prostaglandin E(2), caused a significant increase in venular PMNL concentration. 5. Systemic treatment with the anti-P-selectin monoclonal antibody PB1.3 had no effect on the histamine-induced venular PMNL accumulation (i.e. rolling) in female Wistar or male Sprague-Dawley rats. On the other hand, identical treatment with PB1.3 very effectively inhibited the histamine-induced PMNL response in the mesentery of rabbits. 6. In conclusion, we have shown that a histologically determined increase in leukocyte concentration in rat mesenteric venules may be used as an index of mediator-induced leukocyte rolling if the relative contribution of rolling and firm leukocyte adhesion is first determined, for example by the means described in this study. This relatively simple approach may be very useful for studying various aspects of leukocyte rolling when the ‘spontaneous' rolling triggered by preparation of tissues for intravital microscopy is undesirable.